Dapatkah Love Of Money Sebagai Variabel Intervening Pengaruh Variabel Kecerdasan Terhadap Persepsi Etis Mahasiswa Akuntansi? - Hermawan, Sigit; Nurlia, Wika (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 2 (2017)DO - 10.24843/JIAB.2017.v12.i02.P04, 2017)
ABSTRACT The purpose of this study is to test the love of money as an intervening variable for the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on the ethical perceptions of accounting students. This study also tested partially and simultaneously the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on the ethical perceptions of accounting students. This research is in the field of associative quantitative research and testing five hypotheses. The sample of this research is 141 accounting students. The analysis is done by multiple regression analysis. The results suggest that love of money could not be an intervening variable for the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on the ethical perceptions of accounting students. There are both partial and simultaneous influence for intellectual intelligence, emotional intelligence, and spiritual intelligence on the ethical perceptions of accounting students   Keywords: love of money,  intellectual intelligence, emotional intelligence, and spiritual intelligence, ethical perceptions
Keywords: love of money, intellectual intelligence, emotional intelligence, and spiritual intelligence, ethical perceptions